PENGARUH HARGA, KUALITAS PELAYANAN, DAN BRAND AMBASSADOR TERHADAP KEPUTUSAN PEMBELIAN PRODUK BTS MEAL OLEH KONSUMEN MUSLIM - Desvira Utami Rahmadini; Ahmad Amin Dalimunthe (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2022)
Consumer purchasing decisions are usually carried out when consumers choose and evaluate a product or service. Price, service quality, and brand ambassadors are considered to be important to determine a consumer's purchase decision. Therefore, this study aims to measure the effect of price, service quality, and brand ambassadors on Muslim consumers’ decision to purchase BTS Meal products. 90 Muslim consumers were selected as respondents using non-probability sampling with purpossive sampling technique. To collect data, a google form of questionnaire was distributed. Using multiple linear regression, the data were analyzed with SPSS. The results show that price and service quality of the BTS Meal have a positive yet not significant effect on the Muslim consumers’ purchasing decisions. While the brand ambassador has a positive and significant impact on the consumers’ decisions. Simultaneously, the three measured variables have a significant effect on the Muslim consumers when deciding to purchase the product. However, 75% of the coefficient of determination stated that the value of purchasing decisions was influenced by other factors. Thus, the findings suggest that the manufacturers need to optimize the use of Brand Ambassadors while emphasizing the equal importance of price and service quality for the success of promoting the product.